Racjonalność - kategoria indywidualistyczna czy zbiorowa? - Unold, Jacek (Rationality : an Individualistic Or Collective Category?, 2005)
The principle of rationality is best known as the Rational Choice Theory. This approach attributes rationality exclusively to individuals and assumes continuous optimization. Since the introduction of Simon's bounded rationality the optimization requirements have been significantly eased. However, there is still a strong necessity for research within the domain of social rationality, which would take into account the specificity of collective behavior.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 435-448